Short history of regulations and approved indications of antimicrobial drugs for food animals in the USA. Issue 3 (29th November 2016) - Volkova, V. V.; DeMars, Z.
Abstract : We review historical availability and regulation, and recent indications of antimicrobial drugs for food animals in the USA. We summarize the timeline of introduction of individual antimicrobial drug classes from the 1930s to present, history of regulation of antimicrobial drugs from the 1930s to present and indications of antimicrobial drugs in 1996–2014 for food animals in the USA. The history of antimicrobial drug regulation demonstrates a historical precedent for harmonized regulations of antimicrobials 'for human and other animals' in the USA.